Researching prisoner experiences with prison officers: An action research-inspired approach. Issue 1 (March 2014) - Drake, Deborah H
This article reports on research that incorporated action research-inspired dimensions on a project conducted in three maximum-security prisons in England. The project was aimed at collecting ethnographically informed data on prisoner experiences, at developing a method by which such data could be systematically and routinely collected by prison staff and at facilitating opportunities for prison officers to understand the 'pains of imprisonment' from the perspectives of prisoners. The challenges and limitations of the project are discussed, with particular reference to the paradox of participation and the role of power relations within prisons and within the research process. It is suggested that despite the inherent difficulties of attempting a participative approach with more powerful actors, facilitating change on a larger scale may be best served by developing a 'pedagogy of the oppressors' alongside a 'pedagogy of the oppressed'.